Kesolvenan dan kecekapan teknikal syarikat insurans hayat di Malaysia - Yakob, Rubayah; Isa, Zaidi (Universiti Utara Malaysia, 2008)
Purpose - The paper sought to identify the effieciency level of the insurer and investigated the relationship between efficiency and solvency, particularly companies in the life insurance sector. This study also attempted to examine the relationship between size and solvency Design/Methodology/Approach - Efficiency level or score for all life insruance companies were derived from the stochastic frontier analysis(SFA). In addition, panel data analysis was used to investigate the relationship between size and efficiency score with solvency of the insurer. Two year data,ranging from 2003 to 2004, were used in this study. Findings - The results proved that the majority of life insurers do not operat in-line with the efficiency frontier and this was because of the inefficiency in handling resources (technical inefficiency). The study also discovered that size and efficiency are significantly related to life insurer solvency. The model which was developed can be used in assisting several parties such as consumers, life insurers, and policy makers to improve the existing insurance system.Originality/Value - The paper used a different approach to measure efficiency, which was a parametric approach as compared to a non-parametric approach, namely Data envelopment analysis (DEA). Exploring the possibility of incoporating effciency scores as one of the determinant for solvency would be beneficial to the life insurance industry players. Paper type - Research Paper.